2014
DOI: 10.3171/2014.7.peds14168
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of newborn hearing screening in patients with myelomeningocele

Abstract: Object Brainstem dysfunction occurs in a minority of patients with myelomeningocele (MMC), most of whom have Chiari Type II malformation. Some surgeons advocate early identification of these patients for craniocervical decompression to avoid significant mortality. The auditory brainstem response has been found to be abnormal in most children with MMC. The present study examines whether failure of routine newborn hearing screening (NHS) predicts brainstem dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…The infants in the Study Groups presented grater absence of TEOAE: two bilateral fails were found in SG1 and two bilateral fails and one unilateral fail were detected in SG2 (Tables 1 and 2). This finding is in agreement with those of a recent study, in which the authors compared the results of NHS in 90 newborns in NICU, 40 with MMC and 50 without the disease, and found greater absence of TEOAE in the first (24) . Cochlear hearing loss was observed in 4.8% of the infants in SG1 and in 5.3% of those in SG2, with no difference between the groups or ears ( Table 5).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The infants in the Study Groups presented grater absence of TEOAE: two bilateral fails were found in SG1 and two bilateral fails and one unilateral fail were detected in SG2 (Tables 1 and 2). This finding is in agreement with those of a recent study, in which the authors compared the results of NHS in 90 newborns in NICU, 40 with MMC and 50 without the disease, and found greater absence of TEOAE in the first (24) . Cochlear hearing loss was observed in 4.8% of the infants in SG1 and in 5.3% of those in SG2, with no difference between the groups or ears ( Table 5).…”
Section: Resultssupporting
confidence: 93%
“…Concerning the type of hearing loss, 31% of the infants in SG1 and 26.3% of those in SG2 presented central auditory disorders. In fact, several studies in the literature have indicated that this population presents higher incidence of this type of impairment (8,24,26) .…”
Section: Resultsmentioning
confidence: 90%